2021
DOI: 10.1016/j.asmr.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Randomized Controlled Trials in Anterior Cruciate Ligament Reconstruction: Standard Techniques Are Comparable (299 Trials With 25,816 Patients)

Abstract: To provide an overview of all published randomized controlled trials (RCTs) in anterior cruciate ligament reconstruction (ACLR) summarizing the available evidence. Methods: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched the Cochrane FIGCentral Register of Controlled Trials, Ovid MEDLINE, and Embase for RCTs of ACLR from their inception to August 26, 2020. Outcome measure was whether RCTs reported statistically significant findings. RCTs were then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
0
7
0
1
Order By: Relevance
“…This evidence has shown that for the vast majority of patients, using standard arthroscopic techniques, a single- or double-bundle ACLR with hamstrings, or bone-patella tendon-bone autografts, implanted using a transportal technique and graft fixation methods familiar to the surgeon, achieve satisfactory and comparable clinical outcomes as reported by the included RCTs. 14 …”
Section: Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence has shown that for the vast majority of patients, using standard arthroscopic techniques, a single- or double-bundle ACLR with hamstrings, or bone-patella tendon-bone autografts, implanted using a transportal technique and graft fixation methods familiar to the surgeon, achieve satisfactory and comparable clinical outcomes as reported by the included RCTs. 14 …”
Section: Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“… 12 , 13 Recently, we systematically reviewed all published RCTs of TKA, THA, and ACLR. 14 - 16 Here, we present an overview of our findings and the lessons learnt from 1,014 RCTs in 107,511 patients.…”
mentioning
confidence: 95%
“…парциальных артроскопических менискэктомий и около 200 тыс. реконструкций ПКС [4,5]. К сожалению, в доступной литературе не представлены статистические данные о ежегодном количестве таких операций в России.…”
unclassified
“…Graft selection is an important component, impacting long-term outcomes, including graft failure and revision. Many studies have shown that allograft utilization is associated with worse outcomes following ACLR compared with autograft 6-9 . Our own previous study found a 3 times higher revision risk with allograft compared with bone-patellar tendon-bone (BPTB) autograft 10 .…”
mentioning
confidence: 99%